LOCAL WISDOM-BASED TEACHING MATERIALS TO SUPPORT THE INDEPENDENT CURRICULUM IN SCIENCE LEARNING: A SYSTEMATIC LITERATURE REVIEW (SLR) - Kusrianto, Wiwin; Sudatha, I Gde Wawan; Santosa, Made Hery; Suartama, I Kadek (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2025)
The addition of local wisdom to the curriculum is a very relevant issue, considering that Indonesia has a very diverse cultural wealth. Although various studies and publications have been conducted on various topics and levels of education, a comprehensive study of how local knowledge is used in the science curriculum at the senior high school (SMP) level is still relatively limited. This study aims to explore in depth the implementation of local wisdom in the science curriculum at junior high school. The approach used is a systematic literature review, by analysing 20 scientific articles published between 2015 and 2025 and indexed in the Scopus and Google Scholar databases. The integration of local knowledge in middle school science classes has great potential to improve the quality of education while supporting the preservation of local culture. This integration process can be applied through various forms of activities, including intracurricular, co-curricular and extracurricular. In intracurricular activities, local wisdom is adapted into teaching materials, learning methods, learning media, and evaluation systems. Co-curricular activities may include the Pancasila Student Profile Strengthening (P5) programme, environmental education, field studies, and educational visits. Meanwhile, in extracurricular activities, integration can be done through traditional arts such as puppet shows. It is expected that through this approach, there will be improvements in science literacy, ecoliteracy, science process skills, disaster knowledge, critical thinking skills, and overall student learning outcomes.